Geomicrobiological linkages between short-chain alkane consumption and sulfate reduction rates in seep sediments - Bose, Arpita; Rogers, Daniel R.; Adams, Melissa M.; Joye, Samantha B.; Girguis, Peter R. (Frontiers in Microbiology, 2013)
Marine hydrocarbon seeps are ecosystems that are rich in methane, and, in some cases, short-chain (C2-C5) and longer alkanes. C2-C4 alkanes such as ethane, propane and butane can be significant components of seeping fluids. Some sulfate-reducing microbes oxidize short-chain alkanes anaerobically, and may play an important role in both the competition for sulfate and the local carbon budget. To better understand the anaerobic oxidation of short-chain n-alkanes coupled with sulfate-reduction, hydrocarbon-rich sediments from the Gulf of Mexico were amended with artificial, sulfate-replete seawater and one of four n-alkanes (C1-C4) then incubated under strict anaerobic conditions. Measured rates of alkane oxidation and sulfate reduction closely follow stoichiometric predictions that assume the complete oxidation of alkanes to CO2 (though other sinks for alkane carbon likely exist). Changes in the δ13C of all the alkanes in the reactors show enrichment over the course of the incubation, with the C3 and C4 incubations showing the greatest enrichment (4.4‰ and 4.5‰ respectively). The concurrent depletion in the δ13C of dissolved inorganic carbon (DIC) implies a transfer of carbon from the alkane to the DIC pool (-3.5 and -6.7‰ for C3 and C4 incubations, respectively). Microbial community analyses reveal that certain members of the class Deltaproteobacteria are selectively enriched as the incubations degrade C1-C4 alkanes. Phylogenetic analyses indicate that distinct phylotypes are enriched in the ethane reactors, while phylotypes in the propane and butane reactors align with previously identified C3-C4 alkane-oxidizing sulfate-reducers. These data further constrain the potential influence of alkane oxidation on sulfate reduction rates in cold hydrocarbon-rich sediments, provide insight into their contribution to local carbon cycling, and illustrate the extent to which short-chain alkanes can serve as electron donors and govern microbial community composition and density.